2009
DOI: 10.1158/1055-9965.epi-08-1211
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidants and Skin Cancer Risk: An 8-Year Community-Based Follow-up Study

Abstract: Background: Antioxidant nutrients can help prevent skin damage caused by ultraviolet radiation from sunlight, but it is not clear whether serum concentrations of such nutrients influence skin cancer risk. Methods: We carried out a prospective study of the associations between serum concentrations of antioxidant nutrients and incidence (person-based and tumorbased) of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) of the skin among a random subsample of 485 adults from an Australian community. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…For this study, we used data collected as part of the Nambour Skin Cancer Study, which involved a random, communitybased sample of Australian men and women. The design, study population, baseline data collection, and follow-up methods have previously been described in detail (18,19). In brief, participants were 1621 residents of the Nambour, a semirural township in Queensland, who were originally randomly selected from the electoral roll (voting is compulsory in Australia) (20) and participated in the Nambour Skin Cancer Prevention Trial (1992)(1993)(1994)(1995)(1996) and were followed up until 2007.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we used data collected as part of the Nambour Skin Cancer Study, which involved a random, communitybased sample of Australian men and women. The design, study population, baseline data collection, and follow-up methods have previously been described in detail (18,19). In brief, participants were 1621 residents of the Nambour, a semirural township in Queensland, who were originally randomly selected from the electoral roll (voting is compulsory in Australia) (20) and participated in the Nambour Skin Cancer Prevention Trial (1992)(1993)(1994)(1995)(1996) and were followed up until 2007.…”
Section: Methodsmentioning
confidence: 99%
“…The design, study population, baseline data collection, and follow-up methods have previously been described in detail [8,9]. In brief, participants were 1621 residents (88 % of 1850 persons invited) [8] of the Nambour township in Queensland, who were randomly selected from the electoral roll (voting is compulsory in Australia) [10] to participate in the Nambour Study and followed up between 1992 and 2007.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Recently, several studies have suggested that serum selenium level could be used as a prognostic marker in various cancer types, such as prostate, skin, breast and colon [34][35][36][37]. While studies suggest that selenium can help prevent cancer cell progression and may be useful as a diagnostic marker, it is not clear whether serum concentrations of selenium influence cancer progression.…”
Section: Discussionmentioning
confidence: 99%